Feasibility study suggests no impact from protected engagement time on adverse events in mental health wards for older adults. (6th July 2017) - Smith, Toby; Clark, Allan; Dodd, Emily; Khoo, Mary‐Ellen; Heneker, Sarah; Cross, Jane; Cheston, Rik; Gray, Richard; Fox, Chris; Nolan, Fiona
Abstract: Hospital adverse events, such as falls, violence and aggression, security, self‐harm, and suicide, are difficult to manage in older people with dementia. The purpose of the present study was to determine whether protected engagement time (PET) resulted in lower adverse events and incidents compared to comparable non‐PET wards for people admitted to inpatient older people's mental health wards. Ten inpatient wards for older people were included. Five followed a PET‐management pathway, while five continued usual care. All adverse events and incidents were recorded in routine hospital records over 72 weeks. Data were gathered from these records and analysed as rate per person per week to assess differences in frequency and type of adverse events between wards. A total of 4130 adverse events were recorded. In the PET wards, a mean of 0.38 adverse events occurred per person per week compared to 0.40 in non‐PET wards. No statistically‐significant differences were found between PET and non‐PET wards for adverse events ( P  = 0.93), or for adverse events of any particular type ( P  ≥ 0.15). Therefore, there is no evidence to suggest that PET has any impact on adverse events in older people's mental health wards. Further investigation with a larger cohort is warranted, using a definitive, phase 3, clinical trial.